Constructing Collective Memories regarding Conflicto Armado Interno in Perú (1980-2000): Psychologýs Role and Contributions Based upon Experiences of Collective Reprocessing of Memories in Educational Contexts. Issue 4 (2nd October 2021) - Pease D., María Angélica; Guillén, Henry
Abstract: The construction of collective memory with regard to Conflicto Armado Interno (Internal Armed Conflict CAI) -violence that occurred in Perú between 1980 and 2000- is still a challenge that produces disputes and tension. It has been studied mostly by social scientists, from the point of view of 'memory' studies. Despite the great explanatory power of Psychology in understanding these type of processes, its contribution has mainly focused on mental health. Education has been the least researched area, despite the role the Truth and Reconciliation Committee attributed to education in schools and universities, in constructing memories about war. In this context, we reflect on the role of Psychology on constructing collective memory in educational settings. Starting from Hallbach´s classic theory of collective memory, to contributions from cognitive psychology and post-traumatic growth studies, we analyze two experiences in educational contexts with the purpose of proposing some guidelines for research and intervention.